Interannual variability of the Mediterranean outflow observed in Espartel sill, western Strait of Gibraltar - García-Lafuente, Jesús; Delgado-Cabello, Javier; Sánchez-Román, Antonio; Soto-Navarro, Francisco Javier; Carracedo, Lidia; Díaz del Río, Guillermo (American Geophysical Union, 2009)
Four-year time series of observations in Espartel sill at the western part of the Strait of Gibraltar have been analyzed in order to investigate the variability of the Mediterranean outflow. It is assumed that the observed variability comes from the changing properties of the dense waters that are located at the maximum depth from where they can be uplifted in the upstream basin (Albora´n Sea, inside the Mediterranean Sea) and evacuated through the strait. From this perspective, the following three mechanisms are investigated: (1) the replenishment of the deep basin by newly formed Western Mediterranean Deep Water that, depending on its density, can either uplift old resident waters or lay above them leaving in any case a cold signature in the temperature series; (2) the presence/absence of the energetic anticyclonic gyres in the Albora´n Sea, particularly the western one, which can transfer momentum to the underlying Mediterranean vein and provide it with additional energy to ascend over the sills of the strait; and (3) the meteorologically enhanced flows that follow the rapid changes of atmospheric pressure over the western Mediterranean basin, which would be able to aspire deeper waters residing in the upstream basin. The three mechanisms act on different timescales, from annual in case (1) to monthly in case (2) to weekly in case (3) although these two latter are modulated annually by the seasonal prevalence of the western Albora´n gyre in summer and of the strong meteorologically driven fluctuations in winter. The mechanisms overlap at annual timescales making it difficult to separate out the different contributions.
Keywords: Circulación oceánica - Gibraltar (Estrecho); Mediterranean outflow; Alboran Sea gyres; Interannual variability; Strait of Gibraltar; Seasonality; WMDW